The Influence of Personality, Emotional Intelligence, and Job Stress on Counterproductive Work Behaviors - Setyanti, Sri Wahyu Lelly Hana; Sudarsih; Pradana, Riyo Gita (PT Inovasi Pratama Internasional, 2023)
This study aims to prove the influence of personality, emotional intelligence, and work stress on counterproductive work behavior. This research was conducted at the multinational company Kutai Timber, Co., with 75 respondents in the production department. The data in this study were obtained through questionnaires and then analyzed using the multiple linear regression method. The results of this study indicate that personality, emotional intelligence, and job stress have a significant effect on counterproductive work behavior. The coefficient value of the emotional intelligence variable is negative 0.416, which means that if the value of emotional intelligence increases, it will reduce the level of employee counterproductive work behavior. Research proves the Personality variable has a value of 0.326 with an indicator of agreeableness and tend to avoid conflict, and then the job stress variable has a positive value of 0.251. The implications of the theory are discussed to prove its effect on counterproductive behavior. The practical consequences aim to reduce counterproductive behavior through improving personality, and emotional intelligence and reducing employee stress levels.